Sedoanalgesia with dexmedetomidine in daily anesthesia practices: a prospective randomized controlled trial - Ali Kendal Oğuz; Celaleddin Soyalp; Yunus Emre Tunçdemir; Arzu Esen Tekeli; Nureddin Yüzkat (BMC Anesthesiology)
Abstract Background Patient safety is important in daily anesthesia practices, and providing deep anesthesia is difficult. Current debates on the optimal anesthetic agents highlight the need for safer alternatives. This study was justified by the need for safer and more effective anesthetic protocols for outpatient hysteroscopic procedures, particularly those conducted outside the operating room. Propofol, while widely used, has significant limitations, including respiratory depression, hemodynamic instability, and delayed recovery when higher doses are required for adequate sedation. The addition of opioids to propofol, though beneficial for analgesia, introduces risks such as hypoxemia and hypotension. These challenges necessitate exploring alternative combinations that balance sedation depth with fewer side effects. Objective To assess the efficacy and safety of deep sedoanalgesia achieved with dexmedetomidine-propofol versus remifentanil-propofol combinations in daily anesthesia practices. Design Prospective randomized clinical study. Settings This study was carried out at Dursun Odabaş Medical Center. Patients Eighty ASA I–II patients, aged 18–65, scheduled for elective hysteroscopic interventions under sedoanalgesia were included in the study. Main outcome measures The primary aim of our study was to identify an anesthetic agent combination capable of delivering effective and safe deep sedation, with sedation depth assessed via the Ramsey Sedation Score (RSS) and respiratory safety evaluated through desaturation rates. Secondary endpoints included Visual Analogue Scale (VAS) scores, oxygen saturation (SpO2), patient, surgeon, and anesthesiologist satisfaction scores, hemodynamic parameters, the time to achieve an RSS > 4, the time to reach a Modified Aldrete Score (MAS) > 9, and the requirement for mask ventilation and jaw thrust maneuvers. Interventions Patients were randomized into two groups (n = 40 each): Group DP (Dexmedetomidine–Propofol): A bolus of 1 mg/kg IV propofol and 1 mcg/kg IV dexmedetomidine over 10 min, followed by a continuous infusion of 0.2–1.4 mcg/kg/hour. Group RP (Remifentanil–Propofol): A bolus of 1 mg/kg IV propofol and 0.25 mcg/kg IV remifentanil, followed by a continuous infusion of 0.025–0.1 mcg/kg/minute. Results Patients in the DP group exhibited significantly lower VAS scores and desaturation rates (p = 0.003) compared to the RP group. Satisfaction scores (patient, surgeon, anesthesiologist) and integrated pulmonary index (IPI) values were significantly higher in the DP group (p < 0.05). Conclusion The dexmedetomidine-propofol combination is an effective and safe anesthetic regimen for deep sedation in outpatient hysteroscopic procedures, offering adequate sedation and superior preservation of respiratory function. Additionally, the dexmedetomidine-propofol combination ensures more stable hemodynamics, with a lower incidence of hypoxia, and results in higher satisfaction rates among patients, surgeons, and anesthesiologists. Trial registration Clinical Trials ID is NCT05674201 Date 2022.12.07.